The mobilization of science and technology fisheries innovations towards an ecosystem approach to fisheries management in the Coral Triangle and Southeast Asia. (December 2016) - Gorospe, Kelvin D.; Michaels, William; Pomeroy, Robert; Elvidge, Christopher; Lynch, Patrick; Wongbusarakum, Supin; Brainard, Russell E.
Abstract: Several regional fisheries and marine conservation organizations in the Coral Triangle (CT) and Southeast Asia have indicated their support for an ecosystem approach to fisheries management (EAFM). It is also likely that science and technology (S&T) innovations will play a role in the region for the purposes of filling gaps in fisheries data, enhancing the coordination of fisheries management efforts, and implementing and operationalizing an EAFM. Here, we outline the methodology and results of an expert-opinion survey designed to elucidate and prioritize the implementation of these S&T innovations. As a first step and case study, the survey presented here was conducted on U.S. government experts. The U.S. market is one of the world's largest importers of seafood, and therefore, in the framework of this study, is considered to be a stakeholder in the seafood supply chain that originates in the CT and Southeast Asia region. Results are discussed in terms of the data needs and principles of an EAFM, as well as current trends and contexts of the CT and Southeast Asia region. Next steps and recommendations are also provided on how S&T innovations can be implemented to enhance the cooperation and coordination of regional marine resource management efforts.